Knowledge and attitude toward geriatric nursing care and associated factors among nurses working at hospitals in Hawassa City, Ethiopia, 2022 - Abera, Workineh; Daba, Alemneh Kabeta; Gebre, Bereket Beyene; Ashagere, Mathewos; Yeheyis, Tomas; Addisu, Dereje; Amlaku, Tsegahun; Tadesse, Fikru; Samuel, Tinbete (Frontiers in Medicine, 2024)
Background Globally, the fastest growth in the number of older people combined with chronic and age-related medical conditions experienced by the older adult placed great demand on geriatric care. Thus, nurses are required to be knowledgeable and have a desirable attitude toward geriatric nursing care. Therefore, this study aimed to assess knowledge and attitude toward geriatric nursing care and associated factors among nurses working at hospitals in Hawassa City, Ethiopia. Methods Hospital-based cross-sectional study was conducted from June 30 to July 30, 2022, among 365 nurses. The hospitals and study participants were selected by using purposive and simple random sampling methods, respectively. Data were collected using self-administered questionnaires. Descriptive statistics were computed to generate descriptive results. Binary and multivariable logistic regressions were used to identify predictors at p-value <0.05. Results About 39.2% of nurses had good knowledge and 49.3% of the nurses showed a positive attitude toward geriatric nursing care. Nurses with BSc degree or above [AOR 2.5, 95% CI, (1.2–5.6)], having lived with older people [AOR 2.2, 95% CI, (1.4–3.6)], nurses with 6–10 years [AOR, 2.8, 95% CI, (1.4–5.57)] and >10 years of work experience [AOR 4.2, 95% CI, (1.6–10.8)] were more likely to have knowledge about geriatric nursing care. Having BSc degree or above [AOR 2.7, 95% C.I, (1.2–6)], 6–10 years [AOR 3, 95% CI, (1.48–6.3)], and >10 years [AOR 3.9, 95% CI, (1.4–10.99)] of work experience, living experience with older people [AOR 1.7, 95% C.I:1.05–2.7], knowledge about geriatric care [AOR 3, 95% CI,(1.85–4.92)], and having worked at adequate space [AOR 1.7, 95% CI: 1.009–2.8] increased odds of good attitude toward geriatric nursing care. Conclusion Less than half of nurses demonstrated good knowledge and positive attitude toward geriatric nursing care. Higher level of education, higher work experience, living with older people were significantly associated with knowledge and attitude toward geriatric nursing care. Additionally, working in an adequate space and having knowledge about geriatric care positively influenced attitude toward geriatric nursing care. Therefore, nursing schools and hospitals should conduct training and consider incorporating more content about geriatric care into nursing education to enhance nurses’ knowledge and attitude.